Effectiveness of the Cooperative Learning Model Gallery Walk Type on the Learning Motivation of 10th-Grade Visual Communication Design Students at SMK Negeri 3 Kepahiang - Sisleni; Winda Ramadianti (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aimed to evaluate the effectivitas of the Cooperative Learning Model Gallery Walk type on the motivation of 10th- Grade students in Visual Communication Design at SMK Negeri 3 Kepahiang. The research is of a descriptive qualitative nature, with the entire population consisting of 10th- Grade Communication design students at SMK Negeri 3 Kepahiang. Data for this study were collected through surveys, observations and interviews. The finding indicated that students display increased motivations during English lessons, show greater participation, contribute to a more engaging classroom environment, and maintain better focus during learning activities. Keywords : Gallery Walk and motivation